Challenges and Responses of Contemporary Pakistan-Iran Relations - Asiya Bukhari; Rizwan Ali Shinwari; Tahir Mahmood Azad, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
Iran and Pakistan are neighboring Muslim countries. Since the independence of Pakistan from British India in 1947, it has kept close ties with Iran, based on shared values and a common heritage. Both the countries went through ups and downs in their history but still maintained a peaceful relation. To maintain a good momentum of relations, they adopted policies to enhance their friendship. This paper focuses on different pushing and pulling factors between their relations, at the local, regional, and global levels, while analyzing their changing perspectives towards each other over time on different common issues. Those factors include the politics circles around delaying the Iran-Pakistan gas pipeline, the Iran nuclear issue, the U.S. intervention in the wake of its withdrawal from the landmark Joint Comprehensive Plan of Action (JCPOA), the Afghanistan situation and implications for both Iran and Pakistan, Saudi Arabian influence especially in the foreign policy formulation of Pakistan, and the recent Indian rapprochement towards Iran. This paper is based on secondary data.